Primal Tree의 공간 분할 샘플링 분석 및 구현 - 박태정(Taejung Park) (디지털콘텐츠학회논문지, 2014)
컴퓨터 그래픽스나 기하 정보 분석 및 검색 등의 애플리케이션에서 일반적인 octree가 널리 사용된다. 그러나 거리장 등 공간에 분포하는 특정한 연속 정보를 샘플링하기 위한 목적으로 일반적인 octree를 적용할 경우 샘플링 데이터 중복과 샘플링 지점과 표현 단위의 불일치가 발생한다. 이 문제를 해결하기 위해 dual octree가 제안된 바 있다. 본 논문에서는 dual octree가 일반적인 octree의 단점은 해결했으나 무한하게 분할을 수행하더라도 특정한 연속 영역에 액세스하지 못한다는 사실을 증명하고 이러한 모든 문제들을 해결할 수 있는 대안으로 Lefebvre와 Hoppe가 제안한 primal tree를 응용할 수 있음을 제시한다. 또한 트리 구조의 병렬화에 널리 사용되는 Morton code를 응용한 3차원 primal tree 검색 알고리즘을 제안한다. The general octree structure is common for various applications including computer graphics, geometry information analysis and query. Unfortunately, the general octree approach causes duplicated sample data and discrepancy between sampling and representation positions when applied to sample continuous spatial information, for example, signed distance fields. To address these issues, some researchers introduced the dual octree. In this paper, the weakness of the dual octree approach will be illustrated by focusing on the fact that the dual octree cannot access some specific continuous zones asymptotically. This paper shows that the primal tree presented by Lefebvre and Hoppe can solve all the problems above. Also, this paper presents a three-dimensional primal tree traversal algorithm based the Morton codes which will help to parallelize the primal tree method. KCI Citation Count: 1